An investigation into the role of DTP as a co-collector in the flotation of a South African PGM ore - Bezuidenhout, Jacques (Department of Chemical Engineering, 2014)
The primary aim of this study was to investigate, using a combination of batch flotation and ToF-SIMS experimental techniques, whether a collector-collector synergistic interaction between SIBX and diethyl DTP will result in significantly enhanced copper, nickel, platinum and/or palladium recoveries and grades in a PGM containing ore from South Africa.